2007
DOI: 10.1097/01.tgr.0000299162.52493.6f
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Tracheotomy Tubes and One-way Speaking Valves to Swallowing Success

Abstract: The contribution, if any, of a tracheotomy tube on aspiration status and swallowing success is investigated. Specific topics discussed include presence of a tracheotomy tube, tracheotomy tube cuff status, tracheotomy tube occlusion status, one-way tracheotomy tube speaking valves, and ventilator dependency. A critical analysis on the role of aging revealed that the high incidence of aspiration in older individuals with tracheotomies can be attributed to the critical illness that necessitated the tracheotomy tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…, Gross et al . , Suiter and Leder ), others (Leder , Ohmae et al . ) have concluded that incidences of aspiration were not affected by speaking valve use and deemed no direct deglutitive benefit for the promotion of effective swallowing for tracheostomized patients in acute care settings.…”
Section: Discussionmentioning
confidence: 90%
“…, Gross et al . , Suiter and Leder ), others (Leder , Ohmae et al . ) have concluded that incidences of aspiration were not affected by speaking valve use and deemed no direct deglutitive benefit for the promotion of effective swallowing for tracheostomized patients in acute care settings.…”
Section: Discussionmentioning
confidence: 90%
“…Two cross‐sectional studies (Brady et al . , Suiter and Leder ) were rated as 2c, one case‐control study (Higo et al . ) was rated 3b, and two case series (McGowan et al .…”
Section: Resultsmentioning
confidence: 99%